Automated computation of two-dimensional fetch fields: case study of the Salto Caxias reservoir in southern Brazil. (2nd January 2017) - Marques, Marcelo; Andrade, Fernando O.
ABSTRACT: Marques M, Andrade FO. 2017. Automated computation of two-dimensional fetch fields: case study of the Salto Caxias reservoir in southern Brazil. Lake Reserve Manage. 33:62–73. This work described and applied a computational model, OndaCad, developed to automate Saville's method for fetch evaluation in sinuous inland waterbodies. The OndaCad model is part of a web-based system being developed to estimate induced mixing length and sediment resuspension by effects of wind-generated waves. The model, written in AutoLisp language, allows the agile calculation of fetch on a structured computational mesh that encloses the waterbody. The fetch was determined automatically at each mesh node by using a fine resolution Saville's method, and the solution was displayed on thematic maps as a 2-dimensional fetch field. The model was applied to the case study of Salto Caxias reservoir located in southern Brazil. Two-dimensional fetch fields were calculated for 16 wind directions, and the largest fetches and their locations were identified. The model was able to process 16 maps of fetch in ∼6 hours using a personal computer. The significant wave heights associated with the fetch fields for the north-oriented winds were obtained using parametric equations that assumed variable coefficients dependent on the wind velocity magnitude. Validation of the results was performed against numerical model data for steady state and uniformly distributed winds of 10, 15, and 20 m/s. The significant wave height comparisons indicated errors <10% for the reservoir central area.